Comparative Analysis of Customer-Based Brand Equity Between Public and Private Hospitals - Hamdi, Dendi; Sulistyowati, Yeny; Pangkey, Dicky Yulius (IJBLE Scientific Publications Community Inc., 2026)
Customer-Based Brand Equity (CBBE) has become an increasingly important determinant of hospital competitiveness; however, comparative empirical evidence between public and private hospitals in developing countries remains limited. This study aims to compare CBBE between public and private hospitals in Cirebon Regency, Indonesia, and to identify key brand equity dimensions influencing patients’ hospital choice. A comparative cross-sectional survey was conducted involving 360 patients, comprising 180 from public hospitals and 180 from private hospitals, recruited purposively. CBBE was measured using a standardized 24-item questionnaire encompassing seven dimensions: brand awareness, brand association, perceived quality, emotional response, brand relationship, marketing stimulus, and corporate ability association. Data were analyzed using the Mann–Whitney U test and binary logistic regression. The results indicate that private hospitals achieved significantly higher scores across all CBBE dimensions (p < 0.05). Logistic regression analysis identified brand awareness, corporate ability association, emotional response, and brand relationship as significant predictors of hospital choice, with brand relationship emerging as the most dominant factor. These findings suggest that hospital brand equity is shaped not only by perceived service quality but also by institutional reputation and the ability to establish strong emotional and relational bonds with patients. Strengthening patient-centered branding strategies is therefore essential, particularly for public hospitals, to enhance competitiveness and sustain patient loyalty within Indonesia’s national health insurance system.